Micropropagation of commercially important orchid Dendrobium palpebrae Lindl. through in vitro developed pseudobulb culture - Tapash Kumar Bhowmik; Md. Mahbubur Rahman (Journal of Advanced Biotechnology and Experimental Therapeutics, 2020)
ABSTRACT: Dendrobium palpebrae Lindl. an epiphytic fragrant indigenous orchid species of Bangladesh and distributed in Bangladesh, eastern Himalayas, Myanmar, Thailand, Laos and Vietnam at altitudes of 800 to 2500 meters. From in vitro growing plantlets, upper and lower part of pseudobulb segments were aseptically cultured on MS medium supplemented with auxins (IAA, IBA, NAA, Picloram) and cytokinins (BAP, Kinetin). In vitro grown pseudobulb segments both upper and lower part directly produced multiple shoot buds via organogenesis. Average highest number of MSBs (8.21 ± 0.44/segment in lower part; 6.43 ± 0.40/segment in upper part) produced on MS medium with 1.0 mg/l NAA + 2.0 mg/l BAP followed by (7.24 ± 0.41/segment in lower part; 5.96 ± 0.37/segment in upper part) MS medium supplemented with 1.0 mg/l Picloram + 2.0 mg/l BAP. Highest individual shoot bud increased length was recorded on agar solidified MS medium with 1.0 mg/l Picloram + 1.0 mg/l BAP (3.76 ± 0.14 cm) followed by liquid MS + 0.5 mg/l NAA + 1.0 mg/l BAP (3.11 ± 0.12 cm) medium. Elongation of shoot bud was better in agar solidified media than liquid condition and MS was found better than PM. Shoot bud derived seedlings were best responses as increase in length as well as the number of roots developed on agar solidified MS with 0.5 mg/l NAA (4.82 ± 0.22 cm/shoot bud and 2.75 ± 0.17 no/shoot bud) followed by MS with 0.5 mg/l IBA supplemented medium (4.49 ± 0.12 cm/shoot bud and 2.57 ± 0.08 no/shoot bud). The plantlets were successfully transferred to outside environment by successive phases of acclimatization. [ J Adv Biotechnol Exp Ther 2020; 3(3.000): 225-232]